Estimativa por infravermelho da concentração da unidade estrutural b-O-4 em ligninas de angiospermas tropicais Infrared estimates of the concentration of the b-o-4 structural unit in lignins of tropical angiosperms - Heber dos Santos Abreu (Química Nova, 1997)
Five Björkman lignins, codified as AM, LL, GG, PP and AP, were isolated from wood species of Aspidosperma macrocarpum Mart., Lophanthera lactescens Ducke, Gallesia gorazema (Vell.) Miq., Peltogyne paniculata Bth. and Aspidosperma polyneuron Muell. Arg., respectively. Analyses of the lignins were carried out by Fourier transformed infrared spectroscopy using an experimental technique, Diffusely Reflected Infrared Fourier Transformed (DRIFT), admitting in the original spectra a band at 1500 cm-1 as an internal reference. Application of a deconvolution technique made possible to estimate the percentage per mol of b-O-4 unit content around 65.5% to AM, 68.0% to LL, 71.0% to GG. 73.4% to PP and 75.0% to AP, toward AM<LL<GG<PP<AP sequence.